Cathode Materials: Enhancing the Kinetics of Li‐Rich Cathode Materials through the Pinning Effects of Gradient Surface Na+ Doping (Adv. Energy Mater. 6/2016). Issue 6 (March 2016) - Qing, Ren‐Peng; Shi, Ji‐Lei; Xiao, Dong‐Dong; Zhang, Xu‐Dong; Yin, Ya‐Xia; Zhai, Yun‐Bo; Gu, Lin; Guo, Yu‐Guo
Abstract : In article number 1501914, Yun‐Bo Zhai, Lin Gu, Yu‐Guo Guo and co‐workers report that a novel gradient Na‐ion doping concept has been developed to enhance the kinetics of Li‐rich cathode materials. The as‐obtained Na‐ion doped Li‐rich particles exhibit high specific capacity, high initial Coulombic efficiency, good cycling stability, and superior rate capability benefitting from the enhanced kinetics, as well as the pinning effect of Na‐ion doping in stabilizing their structure.